Radial Artery Harvest: A Potential Cause of Arteriovenous Access‐Associated Hand Ischemia. Issue 3 (25th March 2013) - Asif, Arif; Siskin, Gary; Kumar, Vishesh; Haqqie, Syed S; Mathew, Roy O; Wang, Shouwen; Nayer, Ali; Merrill, Donna; Salman, Loay
Abstract Hand ischemia has multiple causes. In this article, we report an additional factor that can induce hand ischemia in hemodialysis patients. A 64‐year‐old white man with coronary artery disease underwent a coronary artery bypass graft procedure using the left radial artery as the bypass graft. Several months later, a left extremity Gracz fistula was created for arteriovenous access. Ever since dialysis was performed via the fistula the patient has experienced a cold hand and pain during dialysis that was somewhat relieved by wearing a woolen glove while on dialysis. Absence of the radial artery in the context of an ipsilateral arteriovenous access was highlighted as a possible etiology. A complete arteriography to determine the presence of stenoses, distal arteriopathy, and true steal was recommended, but the patient refused to undergo any investigation or procedure and instead decided to continue wearing the glove during the treatment. A plan for close follow‐up and possible interventions in the event of worsening pain/ulceration was agreed upon. Radial artery harvest can result in hand ischemia if an ipsilateral arteriovenous access is created. We suggest that the contralateral extremity should be considered if an arteriovenous access is required to minimize this risk of this phenomenon.